Seleksi isolat bakteri amilolitik dari rhizosfer Canna edulis, Kerr. untuk produksi poli hidroksi alkanoat dari limbah cair tapioka - Nurhayati Nurhayati; Ocky Karna Radjasa; Irfan Dwidya Prijambada (Jurnal Rekayasa Proses, 2017)
Petrochemical-based plastic waste accumulated in landfills have been posing serious threat to the environment as this kind of plastics are non-biodegradable. Replacing petrochemical-based plastics with biodegradable plastics constitutes a challenging solution both in terms of mechanical design of the process and most importantly the availability of powerful local microorganism for the process. Therefore, the current study was searching for appropriate local microorganisms for poly hydroxyl alkanoate (PHA) production from starch waste, which was considered as one of cheap carbon sources. Waste water of cassava industry is a good resource of such starch waste water. The microbes were isolated from Canna edulis, Kerr. rhizosphere from Cangkringan. The expected isolates were the bacteria enable the coupling of carbon catabolic pathways with PHA anabolic pathways. It was found that ten isolates were able to use waste water of cassava flour industry as carbon source. The PHA quantitative analysis by spectrophotometer showed that the isolate of Bacillus sp. C8 produced the highest PHA of 2,095 g/L. Further FTIR analysis showed specific bands near 1363,67 cm-1, 1641,42 cm-1, 2929,87 cm-1, 3408,22 cm-1 wavelengths which revealed the presence of CH3, ester carbonyl group (C=O), C-H and terminal OH group of PHA.